(untitled) (Global Journal of Medical Research, 2020)
Staphylococcus aureus is one of the major resistant pathogens in clinical practice; Methicillin Resistant Staphylococcus aureus (MRSA) has come out as superbugs. Apart from this, with the increase in the number of hospitalized immunocompromised patients, Coagulase negative Staphylococcus (CONS) have become a major cause of nosocomial infections. Although molecular method like mecA gene detection is gold standard for MRSA, minimum inhibitory concentration (MIC) of cefoxitin or oxacillin can also be considered as standard where molecular methods are not available. Cefoxitin 30 μg disc or PBP 2a agglutination test can also be used as standard marker for MRSA identification. In this study, out of total 184 clinically significant, non-duplicate specimens, 150 (81.52%) isolates were Staphylococcus aureus and 34 (18.48%) were CONS. Among the CONS, the predominating isolate was Staphylococcus haemolyticus 15 (44.12%), followed by Staphylococcus epidermidis 10 (29.41%). In our study, cefoxitin disk diffusion test was found to have sensitivity 100%, specificity 92.15% and negative predictive value (NPV) 100%. PBP2a latex agglutination test was found to have sensitivity 99%, specificity 97.87% and negative predictive value (NPV) 97.87% in our study. In both the methods, MIC of cefoxitin has been considered as gold standard.